Studi Perbandingan Penilaian Kerusakan Jalan Dengan Metode Bina Marga, PCI (Pavement Condition Index) Dan Metode PASER (Pavement Surface Evaluation And Rating Sistem) Pada Ruas Jalan Garuda Sakti, Pekanbaru - Mubarikah Mubarikah; Elianora Elianora; M Yusa (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Pavement Surface Evaluation System according to the types of road damages which in are seatnce generally used by visual approximation methods in are seatenceBina Marga method, Pavement Condition Index (PCI) method, and Pavement Surface Evaluation and Rating System (PASER) method. This research aims to analyze the comparisons between each method in evaluating Garuda Sakti Street, Pekanbaru. Thetypes of damages which were found at the location are: alligator cracks, longitudinal cracks, grade segregation, ruts, grade depression, road patches, potholes, and edgecracks. According to Bina Marga method, the highest damages record was grade segregation with the magnitude of 134,75% from total area of survey location, and thelowest record was grade depression with the magnitude of 0,70% which produced the same priority value i.e. 6 and could be classified with periodic maintenance program.All the severe damages was found at STA 100-200 m with the PCI = 16 (very poor), the 3rd priority for Enhancement program, and the PASER = 3 could be classified as Structural Repair and Overlay. The evaluation results for Garuda Sakti Street at STA 00+000-01+000 m by using Bina Marga method yielded the priority score of 43 and could be classified as routine maintenance program category, with PCI of 70,1 in good category and PASER of 5 in Sealcoat addition category.Keywords : pavement condition evaluation, Bina Marga method, PCI method, andPASER method.